A comparative analysis of the effects of esmolol, lidocaine, nitroglycerin and placebo on hemodynamic response to extubation, and extubation quality and postoperative pain - Kucukosman, Gamze; Gulhan Aydin, Bengu (Annals of Medical Research, 2021)
Aim: To comparatively analyze and determine the effects of esmolol, lidocaine, and nitroglycerin on hemodynamic response to extubation, extubation quality and postoperative pain, based on the placebo effect.Material and Methods: Our study design covers a prospective, randomized clinical trial in 120 patients who underwent intubation. Random division was applied onto the patients to obtain 4 groups: Esmolol, Lidocaine, Nitroglycerin, and Saline. In preparation for extubation; when the train-of-four (TOF) value reached 75% (basaline), study drugs were administered. When TOF ≥90%, the patients were extubated. Heart rate (HR) and mean blood pressure (MBP) records were taken prior to induction, when TOF 75% and 90, 1st, 3rd, and 5th. minutes after drugs were administered and extubation. Extubation time, quality, and postoperative pain values were recorded.Results: When compared to the Placebo group based on post extubation measurements, the Esmolol group had no significant difference for MBP at any time but lower HR as recorded at the fifth minute (P:0.012). For both indicators, it significantly decreased according to pre- and post excubation records, with the Nitroglycerin group (P0.05). All the groups are indifferent at a statistical significance level for extubation quality. The Lidocain group had lower pain scores in the postoperative period for any specified time, compared to the Placebo (P0.05).Conclusions: No superior agent was found in our study with regard to inhibition of the hemodynamic response to extubation, and its quality. Nonetheless, in order to limit the response esmolol and nitroglycerin were efficacious when used at the doses of 1.5 mg and 2 μg per kg, respectively. Lastly, the postoperative pain were lower in the Lidocaine group.
Keywords: Extubation quality; hemodynamic response; postoperative pain